محكات اختيار شريك الحياة لدى طلبة الجامعات اليمنية بحث مقارن بين عينة الطلبة اليمنيين وعينات عربيه - الارياني, إلهام عبد الله (Sciences de l'Homme et de la Société, 2014)
هدفت الدراسة إلى تحديد محكات اختيار شريك الحياة لدى الطلبة اليمنيين على عينة مكونة من (837) طالب وطالبة وتحديد الفروق بين الطلاب والطالبات في أفضلية اختيار شريك الحياة ومعرفة اثر العوامل الثقافية حيث تم مقارنة نتائج الدراسة مع دراسة زينب درويش؛ ومنيرة الشمسـان (2009) على عينتين مصرية وسعودية باستخدام نفس أداة محكات الاختيار.   This study aimed to determine mate selection criteria among Yemeni students using  a sample of (837) student and identify the differences between male and female students in the preference of choosing a mate and  finding out the impact of the cultural factors. The results of this study were compared with the study of Zainab Darwish; Munira Al-Shamsan )2009( which was based on two samples one Egyptian and another one of Saudi applying the same selection criteria tool.